Agonies and nuances of geriatric head injury: experience of a tertiary care institute of Western India - Mahore, Amit; Dange, Nitin; Vutha, Ravikiran; Garale, Mahadeo (International Surgery Journal, 2017)
Background: Traumatic brain injury (TBI) is the most common cause of mortality and morbidity in emergency surgical department. The basic aim of the present study is to analyze the clinical profile, prognostic factors, impact of comorbidities on outcome and complications of traumatic brain injury in elderly patients. Methods: The study is retrospective analysis of hospital records of all admitted patients of head injury above 60 years of age over last five years at a tertiary care institute of India. Results: There were 94 males and 61 females in our study with male to female ratio of 1.54:1. The average age of male patients were 68.55 years and female patients were 64.50 years. Fall was the most common cause of head injury (59.3%) followed by road traffic accidents (36.8%) and assault was the least common (3.9%). Mortality was more in moderate and severe head injury groups with more propensity among females with comorbidities. Conclusions: Our study highlights that geriatric TBI carries a significant morbidity and mortality in India despite of advances in trauma care.